Implementation and Reinforcement of Religious Moderation Attitudes Among Students at Lempuyangwangi Public Elementary School, Yogyakarta - Suratin, Sonia Isna; Lestari, Rizqi; Sabarudin, Sabarudin (HEUTAGOGIA: Journal of Islamic Education, 2023)
This study adopts a qualitative case study approach to explore implementing and reinforcing religious moderation attitudes among students at Lempuyangwangi Public Elementary School in Yogyakarta. Through observation, interviews, documentation review, and literature analysis, the research delves into the perceptions and experiences of teachers, the principal, and students concerning religious moderation. Utilizing the Miles and Huberman model for data analysis and employing strategies such as triangulation and member checking for reliability and validity, the study unveils a comprehensive view of religious moderation education across diverse religious practices. Results highlight the school's commitment to fostering tolerance and understanding through the principles of honesty, openness, compassion, flexibility, and respect among its multi-religious student body. The study identifies the school's unique approach to religious education, emphasizing the essential role of educational settings in promoting a harmonious society. While acknowledging limitations in scope, the research underscores the need for further investigation into the longitudinal impacts of such educational practices. It suggests a collaborative model involving educators, parents, and the community in expanding religious moderation education. This case study not only enriches the academic discourse on religious moderation but also offers valuable insights for developing inclusive educational frameworks that support Indonesia's diverse identity.